And Child Makes Four: The Impact of a New Child on Dog-Owning Families - Lori R. Kogan; Jennifer Currin-McCulloch; Cori Bussolari; Wendy Packman (Pets)
Pets are often an integral part of the family structure, with many people viewing their pets as children and thinking of themselves as “pet parents”. Pets have been shown to provide an array of psychological and physical health benefits, but some research suggests that the effects of pet ownership are more nuanced than once thought. One common negative aspect of pet ownership is guilt. Drawing from research pertaining to the transition to siblinghood, this study explored pet owner guilt as a result of adding a child to a dog-owning family. It also measured changes in dogs’ behaviors and their impact on owners’ depression and anxiety levels. Results suggest that many parents feel dog-related guilt and struggle with the resultant changes in household dynamics with the arrival of a child. Suggestions to help improve the chances of a successful transition include awareness, preparation, and self-compassion. Planning and preparing can help minimize negative dog behaviors and, as a result, levels of parental depression and anxiety. Parents are encouraged to help their dogs succeed by taking the time to prepare beforehand, thereby minimizing their own guilt and decreasing the potential of a severed human–dog bond.